1995
DOI: 10.1128/jb.177.1.222-228.1995
|View full text |Cite
|
Sign up to set email alerts
|

Gin mutants that can be suppressed by a Fis-independent mutation

Abstract: The Gin invertase of bacteriophage Mu mediates recombination between two inverted gix sites. Recombination requires the presence of a second protein, Fis, which binds to an enhancer sequence. We have isolated 24 different mutants of Gin that are impaired in DNA inversion but proficient in DNA binding. Six of these mutants could be suppressed for inversion by introduction of a second mutation, which when present in the wild-type gin gene causes a Fis-independent phenotype. Only one of the six resulting double m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The basis for this hypothesis is the following: (1) It was shown that the proposed dimer interface of invertase is critical to the interplay between Fis and Hin; detergents which weaken this interface increase the DNA cleavage rate of Hin [25]. This is consistent with the observation that all the reported Fisindependent invertase mutations [25,[28][29][30][31] are at or very near this interface. (2) The bottom of this invertase dimer interface is not only symmetry-unique for a 1:1 Fis dimer/ invertase dimer recognition, but may also serve as a strategic area of contact for Fis, since perturbation there can be amplified to result in structural alteration at both the dimer interface and the DNA cleaving sites; the latter may be transmitted through a 'scissors-like' motion involving the central ß-sheet which had been shown to possess unusual flexibilities [32].…”
Section: A Hypothesis For Fis-invertase Recognitionsupporting
confidence: 70%
“…The basis for this hypothesis is the following: (1) It was shown that the proposed dimer interface of invertase is critical to the interplay between Fis and Hin; detergents which weaken this interface increase the DNA cleavage rate of Hin [25]. This is consistent with the observation that all the reported Fisindependent invertase mutations [25,[28][29][30][31] are at or very near this interface. (2) The bottom of this invertase dimer interface is not only symmetry-unique for a 1:1 Fis dimer/ invertase dimer recognition, but may also serve as a strategic area of contact for Fis, since perturbation there can be amplified to result in structural alteration at both the dimer interface and the DNA cleaving sites; the latter may be transmitted through a 'scissors-like' motion involving the central ß-sheet which had been shown to possess unusual flexibilities [32].…”
Section: A Hypothesis For Fis-invertase Recognitionsupporting
confidence: 70%
“…To further characterize the ability of the repressor to oligomerize, chemical cross-linking experiments were performed using both DEB and BS 3 , which covalently link lysine residues in vitro (Spaeny-Dekking et al, 1995;Staros et al, 1987). The linking carbon chain of these molecules is 4 and 11.4 Å, respectively.…”
Section: Interactions Between Repressor and The Entire Mu Operatormentioning
confidence: 99%
“…9). Conformational changes within the dimer interface that are induced by Fis have also been proposed for Gin, based on the properties of mutations within the region [12,36].…”
Section: Amino-acid Substitutions Within the Dimer Interface Have Different Effects On Catalysismentioning
confidence: 99%